2020 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2020
DOI: 10.1109/smc42975.2020.9283336
|View full text |Cite
|
Sign up to set email alerts
|

EEG-based classification of visual and auditory monitoring tasks

Abstract: Using EEG signals for mental workload detection has received particular attention in passive BCI research aimed at increasing safety and performance in high-risk and safetycritical occupations, like pilots and air traffic controllers. Along with detecting the level of mental workload, it has been suggested that being able to automatically detect the type of mental workload (e.g., auditory, visual, motor, cognitive) would also be useful. In this work, a novel experimental protocol was developed in which subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The emphasis of mental workload studies to date has been almost exclusively on detecting and predicting the level of mental workload. However, it has been suggested that determining the 'type' of mental workload would also be useful [29,30]. Multiple resource theory (MRT; [31][32][33][34]) provides a framework to start understanding the types of mental workload it might be useful to detect in passive BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis of mental workload studies to date has been almost exclusively on detecting and predicting the level of mental workload. However, it has been suggested that determining the 'type' of mental workload would also be useful [29,30]. Multiple resource theory (MRT; [31][32][33][34]) provides a framework to start understanding the types of mental workload it might be useful to detect in passive BCI systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mental workload detection also has potential value in other domains, including gaming [4], adaptive training/learning [5][6][7], and user Sensors 2022, 22, 535 2 of 17 interface design applications [8], to enhance and personalize user experience. Because of its potential usefulness in a range of applications, mental workload detection via EEG is a very active and expanding field, with a large number of published studies (e.g., [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]).…”
Section: Introductionmentioning
confidence: 99%